2017
DOI: 10.21451/1984-3143-ar991
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal consequences of assisted reproductive technologies in cattle

Abstract: Experiments in mice and clinical observations in humans are indicative that adult phenotype can be altered in offspring derived from embryos that were subjected to culture or that were produced by the combination of in vitro oocyte maturation, fertilization and embryonic development (in vitro production; IVP). The most commonly observed changes are in body and organ size, growth rate, cardiovascular function and regulation of glucose homeostasis. In cattle, IVP is associated with increased birth weight and neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although human studies are globally reassuring for the health of IVP offspring, the data presented above plead for a constant vigilance on procedures and effects of ART. Sometimes, effects are just overlooked, as exemplified in the bovine industry where only recent data indicates that current procedures are still associated with increased fetal weight (Hansen & Siqueira, ; Siqueira et al, ). In addition, the effects of some commonly used techniques has still not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Although human studies are globally reassuring for the health of IVP offspring, the data presented above plead for a constant vigilance on procedures and effects of ART. Sometimes, effects are just overlooked, as exemplified in the bovine industry where only recent data indicates that current procedures are still associated with increased fetal weight (Hansen & Siqueira, ; Siqueira et al, ). In addition, the effects of some commonly used techniques has still not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…To date, and since the removal of serum and co‐culture from embryo culture conditions that were shown to be related to the occurrence of LOS, adverse neonatal and adult health outcomes associated with IVP embryos are not much reported by the bovine industry, although an increase in birth weight is still observed (Hansen, 2020; Rivera et al, 2022), associated with high levels of morbidity and mortality among IVP embryo‐derived ruminant offspring (Bonilla et al, 2014; Rivera, 2020; Sinclair et al, 2000). Commonly observed phenomena include increases in placenta, body and organ size, perturbations in growth rate, cardiovascular function and glucose homeostasis regulation (Hansen & Siqueira, 2017). Production characteristics, carcass weight and fertility do not seem affected by IVP, although it has been suggested that milk yield tends to be lower in cows born after IVP using reverse X‐sorted semen compared with IVP controls (Hansen & Siqueira, 2017).…”
Section: Livestock Embryo Productionmentioning
confidence: 99%
“…Commonly observed phenomena include increases in placenta, body and organ size, perturbations in growth rate, cardiovascular function and glucose homeostasis regulation (Hansen & Siqueira, 2017). Production characteristics, carcass weight and fertility do not seem affected by IVP, although it has been suggested that milk yield tends to be lower in cows born after IVP using reverse X‐sorted semen compared with IVP controls (Hansen & Siqueira, 2017). Not only did these females produce less milk, but milk fat and milk protein contents were also decreased (Bonilla et al, 2014; Hansen & Siqueira, 2017).…”
Section: Livestock Embryo Productionmentioning
confidence: 99%
See 1 more Smart Citation